2023
DOI: 10.1101/2023.04.22.537934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDK7 is a Novel Therapeutic Vulnerability in Fibrolamellar Carcinoma

Abstract: Fibrolamellar carcinoma (FLC) is a rare and lethal cancer that afflicts young individuals. The tumor arises in the background of a healthy liver, and patients typically present with advanced cancer at the time of diagnosis. Unfortunately, for these patients with advanced or recurrent cancer, no proven systemic therapies exist resulting in only 30-45% of patients surviving to 5 years. Investigations into the molecular underpinning of FLC have revealed a unique gene fusion between heat shock protein 40 (DNAJB1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…A major limitation of this model for evaluating the primate-specific LINC00473 is its murine origin. In more recent years, at least two other human cancer lines were engineered to express the fusion oncogene, both of which we confirm to exhibit elevated levels of LINC00473 52,70 . While it has been shown that the exogenous introduction of LINC00473 in mouse neurons can modulate synaptic activity, it is unknown whether the transcriptional programs and signaling pathways critical for LINC00473mediated cancer phenotypes are conserved in non-primate contexts 55,56 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A major limitation of this model for evaluating the primate-specific LINC00473 is its murine origin. In more recent years, at least two other human cancer lines were engineered to express the fusion oncogene, both of which we confirm to exhibit elevated levels of LINC00473 52,70 . While it has been shown that the exogenous introduction of LINC00473 in mouse neurons can modulate synaptic activity, it is unknown whether the transcriptional programs and signaling pathways critical for LINC00473mediated cancer phenotypes are conserved in non-primate contexts 55,56 .…”
Section: Discussionsupporting
confidence: 56%
“…HepG2-DP and HepG2-Ctl: HepG2-DP cells were previously described and were a generous gift from Dr. Sean Ronnekleiv Kelly 70 . Briefly, the DNAJB1-PRKACA expressing HepG2 cells (HepG2-DP) were generated using a mammalian dual-guide RNA-CRISPR-CAS9-EGFP vector (VectorBuilder, Chicago, IL) with guide RNA sequences targeting the first intronic regions of DNAJB1 and PRKACA (gRNA1 (DNAJB1) 5'-CAGGAGCCGACCCCGTTCGT-3', gRNA2 (PRKACA): 5'-GTAGACGCGGTTGCGCTAAG-3').…”
Section: Cell Linesmentioning
confidence: 99%
“…A major limitation of this model for evaluating the primate-specific LINC00473 is its murine origin. In more recent years, at least two other human cancer lines were engineered to express the fusion oncogene, both of which we confirm to exhibit elevated levels of LINC00473 [ 52 , 70 ]. While it has been shown that the exogenous introduction of LINC00473 in mouse neurons can modulate synaptic activity, it is unknown whether the transcriptional programs and signaling pathways critical for LINC00473-mediated cancer phenotypes are conserved in non-primate contexts [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 72%
“…HepG2-DP and HepG2-Ctl : HepG2-DP cells were previously described using the HepG2 cell line (RRID: CVCL_0027) and were a generous gift from Dr. Sean Ronnekleiv Kelly [ 70 ]. Briefly, the DNAJB1-PRKACA expressing HepG2 cells (HepG2-DP) were generated using a mammalian dual-guide RNA-CRISPR-CAS9-EGFP vector (VectorBuilder, Chicago, IL) with guide RNA sequences targeting the first intronic regions of DNAJB1 and PRKACA (gRNA1 (DNAJB1) 5’-CAGGAGCCGACCCCGTTCGT-3’, gRNA2 (PRKACA): 5’-GTAGACGCGGTTGCGCTAAG-3’).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation